2019
DOI: 10.1002/smll.201804247
|View full text |Cite
|
Sign up to set email alerts
|

The Binary Effect on Methicillin‐Resistant Staphylococcus aureus of Polymeric Nanovesicles Appended by Proline‐Rich Amino Acid Sequences and Inorganic Nanoparticles

Abstract: The ORCID identification number(s) for the author(s) of this article can be found under https://doi.org/10. 1002/smll.201804247. Prevalent research underscores efforts to engineer highly sophisticated nanovesicles that are functionalized to combat antibiotic-resistant bacterial infections, especially those caused by methicillin-resistant Staphylococcus aureus (MRSA), and that aid with wound healing or immunomodulation. This is especially relevant for patients who are susceptible to Staphylococcus aureus infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 32 publications
0
24
0
Order By: Relevance
“…[ 113 ] For instance, in 425 bc , Persian carried water in silver vessels to prevent water contamination during the war, [ 114 ] and silver powders were used to treat wound ulcers by Hippocrates, which was first recorded in medical history. [ 115 ] Currently, Ag is widely used for killing bacteria or preventing bacterial infection, such as wound healing [ 116 ] and antibacterial coating. [ 117 ] With the rapid development of nanoscience and nanotechnology, silver has been widely made into NPs as a broad‐spectrum antibacterial agent, although the antibacterial mechanism of Ag NPs is still controversial.…”
Section: Conventional Silver‐based Antibacterial Hydrogelsmentioning
confidence: 99%
“…[ 113 ] For instance, in 425 bc , Persian carried water in silver vessels to prevent water contamination during the war, [ 114 ] and silver powders were used to treat wound ulcers by Hippocrates, which was first recorded in medical history. [ 115 ] Currently, Ag is widely used for killing bacteria or preventing bacterial infection, such as wound healing [ 116 ] and antibacterial coating. [ 117 ] With the rapid development of nanoscience and nanotechnology, silver has been widely made into NPs as a broad‐spectrum antibacterial agent, although the antibacterial mechanism of Ag NPs is still controversial.…”
Section: Conventional Silver‐based Antibacterial Hydrogelsmentioning
confidence: 99%
“…Therefore, the key to support AgNPs onto the membrane of polymer vesicles is to form a negatively charged surface to accumulate the silver ions. The hydrophilic and negatively charged carboxyl groups were usually introduced to the side chain of polymers, which were coated on the surface of the formed polymer vesicles [ 38 , 50 , 70 ]. For instance, Du and coworkers [ 38 ] synthesized an amphiphilic random copolymer poly(ethylene oxide)- block -poly(2-(dimethylamino)ethyl- stat -t-butyl acrylate) (PEO- b -P(DMA- stat - t BA)).…”
Section: Strategies To Integrate Polymer Vesicles With Antimicrobial Agentsmentioning
confidence: 99%
“…However, after being linked onto the surface of the vesicles and synergized with AgNPs decorated on the membrane and methicillin antibiotics encapsulated in the cavity, the multifunctional vesicles displayed excellent inhibition of MRSA over 23 h with AgNPs concentra- Decorating AMPs onto the surface of polymer vesicles or liposomes is another effective strategy to endow the vesicles with antimicrobial activity [75,84,89]. Recently, Webster et al [70] prepared polymer vesicles by the self-assembly of PEG-block-poly(D,Llactide) [PEG-b-PDLLA], and the linear AMP, cationic proline (49%) and arginine (24%)-riched porcine cathelicidin, PR-39 was decorated on the surface of the vesicles. The AMP PR-39 could not inhibit the proliferation of S. aureus and MRSA independently.…”
Section: Introduction Of Positively Charged Coronasmentioning
confidence: 99%
“…In a recent study, AMPs were included at the peripheral hydrophilic region of polymersomes, while AgNPs were included inside the hydrophobic corona. In vitro tests indicated that the AMP/AgNPs polymersomes exhibited a satisfactory bacteriostatic activity as well as a low cytotoxicity toward human dermal fibroblasts (Bassous and Webster, 2019). In other cases, AgNPs-coated zwitterionic hydrogels, which confer superhydrophilic properties to resist bacterial attachment, were reported to promote wound healing (GhavamiNejad et al, 2016).…”
Section: Solutions To Reduce Cytotoxicity Of Agnps In Wound Carementioning
confidence: 99%